SOLVENT EFFECT ON THE PHOTOOXIDATION OF AMODIAQUINE WITH SINGLET MOLECULAR OXYGEN - SOTO Z., Adriana M.; VALENCIA U., Gloria C.; GIL, Mariluz (Vitae, 2009)
The use of Amodiaquine (AQ) in the treatment and prevention of the malaria, cause adverse effects in tissue exposed to the light; previous investigations relate these nocive effects to the capacity of this drug to generate active species of oxygen as singlet molecular oxygen (O2(1????g)). This study shows chemical rate constants, kr, for interaction between AQ and (O2(1????g)) measured in several solvents, in the range from 0,12 ???? 0,2 x 106 M-1s-1 in chloroform to 1,71 ???? 0,16 x 106 M-1s-1 in methanol, indicating that kr depends on solvent properties, increasing in solvent of greater polarity. Values for kr are one and two orders of magnitude smaller respect to kT (chemical and physical rate constant); these results show that AQ is a good singlet oxygen quencher. Analysis of solvent effects on kr using the LSER, indicates that kr increases in solvents with great capacity to stabilize charges and dipoles and hydrogen–bond acceptor (HBA) solvents. This solvent dependence is similar to that observed in aliphatic amines, such as triethylamine. Therefore, the little significance from parameter donor HBA is attributed to the formation of a intramolecular hydrogen bridge between of phenol and the nitrogen of tertiary amine.